Komputerisasi Program Terpadu Peningkatan Peranan Wanita Menuju Keluarga Sehat Sejahtera (P2WKSS) Desa Sekar Pada Badan Keluarga Berencana Dan Pemberdayaan Perempuan Pacitan - Surati . (Indonesian Journal of Networking and Security (IJNS), 2014)
Abstract: P2WKSS Integrated Program is one of the work program emphasis on the empowerment of women, in order to help improve the welfare of the family to achieve higher quality of life. The concept of system refers to the design of the written details of the book is already a working agenda and work plan, thus arranged systematically, and can be implemented in the application program. The scope of research is how to have a concept that has been created to assist the planning program of cadres of trainers. Making this application using Netbeans and uses MySQL database. And refers to the details of the concepts that are written in the book.Keyword : concepts, program